Women With Ovarian Cancer and With Fertility Preservation: A Survival Analysis Using the Surveillance, Epidemiology, and End Results Database and Construction of Nomograms to Predict Cancer-Specific Survival - Hou, Yue-min; Yu, Hui; Hao, Jia-tao; Feng, Fang; An, Rui-fang (Frontiers in Oncology, 2022)
Purpose: Determine risk and prognostic factors of ovarian cancer (OC) in women having fertility-sparing surgery, as well as survival outcomes of those with stage I epithelial ovarian cancer (EOC). Also, to determine the effect of chemotherapy in OC treatment, and use multiple independent risk factors to establish a prognostic nomogram for patients with stage I EOC. Patients and Methods: OC individuals with fertility-sparing surrgery (FSS) between 1995 and 2016 were identified in the SEER database. Univariate and multivariate logistic regression was performed to identify the distributions of patient characteristics according to chemotherapy. Cancer-specific survival (CSS) was assessed using Kaplan-Meier curves and log-rank tests. Univariate and multivariate cox regression was conducted to determine the independent prognostic factors for CSS. Cox analysis was used to construct a nomogram. The C-index and calibration plots can show evaluation results of performance. Results: A total of 1839 OC women with FSS were identified in the SEER database. Factors associated with significantly higher chemotherapy odds included younger age, being unmarried, having grade 2-4, stage Ⅱ Ⅲ，or clear cell and non-epithelial histologic type by a multivariable logistic regression model. Multivariate cox regression model confirmed age, marital status, chemotherapy, histologic type, grade and FIGO stage were independent prognostic factors for CSS. In stage I EOC, prognosis of patients with stage IA/IB-grade 3 (5-year CSS 85.3%), or stage IC (5-year CSS 80.6%) was worse than that of those with stage IA/IB-grade 1 (5-year CSS 95.2%), or stage IA/IB-grade 2 (5-year CSS 94.7%). However, chemotherapy improved the survival of patients with stage IA/IB-grade 3 (5-year CSS 78.1% vs. 94.6%, p=0.024) or stage IC (5-year CSS 75.1% vs. 86.7%, p=0.170). Conclusion: The study provided population-based estimates of risk factors and prognostic of OC patients with FSS as well as the survival outcomes of patients with stage I EOC and the effect of chemotherapy. Proposed nomograms exhibited superior prognostic discrimination and survival prediction for patients with stage I EOC.